Increase of Cardioprotective Effectiveness of Remote Ischemic Preconditioning during Cardiac Surgery - A. M. Radovskiy; A. E. Bautin; L. I. Karpova; A. O. Marichev; I. Yu. Ivanov; V. L. Etin; E. Yu. Vasilyeva; М. L. Ivanova; E. V. Batalina; V. K. Grebennik; D. A. Laletin (Вестник анестезиологии и реаниматологии, 2022)
The objective. To increase the effectiveness of cardioprotection during coronary artery bypass grafting (CABG) by using a modified technique of remote ischemic preconditioning (RIPC).Subjects and Methods. A prospective randomized study included 119 patients (aged 18 to 75 years) undergoing on-pump CABG. Patients were divided in 5 groups: Group 1 ‒ Sevoflurane control (ContrSevo), RIPC was not used, sevoflurane anesthesia (n = 24); Group 2 ‒ RIPC1 sevoflurane (RIP1Sevo), RIPC with ischemia-reperfusion of one lower limb, sevoflurane anesthesia (n = 26); Group 3 ‒ RIPC2 sevoflurane (RIP2Sevo), RIPC with ischemia-reperfusion of two lower limbs, anesthesia sevoflurane (n = 23); Group 4 ‒ Propofol control (ContrProp), RIPC was not used, propofol anesthesia (n = 22); Group 5 ‒ RIPC2 propofol (RIP2Prop), RIPC with ischemia-reperfusion of two lower limbs, propofol anesthesia (n = 24). The serum troponin I concentration (cTnI) (baseline, and 30 minutes, 12, 24, 36 and 48 hours after СPB weaning). Hemodynamic parameters and indicators of the clinical postoperative course also were evaluated. The impact ischemic-reperfused tissue mass of RIPC on the cardioprotection was assessed by comparing the groups of ContrSevo, RIPC1Sevo, and RIPC2Sevo. To assess the impact of propofol on the RIPC-induced cardioprotection, the groups of ContrProp and RIPC2Prop were compared.Results. Statistically significant differences in cTnI were found between the ContrSevo and the RIPC2Sevo at points of 12, 24 and 36 hours: ContrSevo 1.83 (1.3; 2.24) ng/ml, RIP2Sevo 1.28 (0.75; 1.63) ng/ml after 12 hours (p = 0.02), ContrSevo 1.44 (0.98; 2.26) ng/ml, RIPC2Sevo 1.17 (0.55; 1.66) ng/ml after 24 hours (p = 0.046), ContrSevo 1.26 (0.86; 1.72) ng/ml, and RIPC2Sevo 0.81 (0.47; 1.24) ng/ml after 36 hours (p = 0.035). No differences in the cTnI were found between the groups of ContrSevo and RIPC1Sevo, RIPC1Sevo and RIPC2Sevo at any stage of the study. There were no statistically significant differences between the groups when comparing hemodynamic parameters. In the RIPC2Sevo Group, arrhythmias requiring cardioversion or drug therapy were significantly less frequent compared to ContrSevo (1 vs. 6) (p = 0.047). There were no other significant differences in the postoperative clinical course. When comparing the groups of ContrProp and RIP2Prop, no significant differences were found in cTnI and hemodynamic parameters as well as in the postoperative clinical course.Conclusions. A greater mass of ischemic-reperfused peripheral tissue is accompanied by greater RIPC-induced cardioprotection. A modified protocol for RIPC with ischemia-reperfusion of two lower limbs with sevoflurane anesthesia enhances cardioprotection during on-pump CABG. The modified RIPC protocol with ischemia-reperfusion of two lower limbs with sevoflurane anesthesia reduces the risk of arrhythmias requiring cardioversion or drug therapy. Propofol inhibits the RIPC-induced cardioprotection with ischemia-reperfusion of two lower limbs.